Eyesight diseases incidence among inhabitants of Ostrowiec Świętokrzyski ond the region - Kowal, Małgorzata; Kowalska, Magdalena; Wójtowicz-Chomicz, Katarzyna; Dyka, Barbara; Borzęcki, Andrzej (Polish Journal of Public Health, 2009)
Introduction. Eyesight is the crucial sense responsible for external contact. Eyesight diseases frequently occur in our society. All injuries, even those superfi cial of eyeball and its additional organs might contribute to direct and indirect risk of vision functions. Aim of the work. Evaluation of eyesight diseases incidence among examined population was the aim of the work. Materials and methods. Studies covered 3274 inhabitants of Ostrowiec Świętokrzyski (69% of women and 31% of men) and the region, within the age group of 0-100 yearold patients hospitalised at the ophthalmic outpatient clinic of Non-Public Independent Health Care Institution. The analysis of medical documentation stored at the ophthalmologic clinic was the research tool. Results. The most numerous group of patients included people aged 70-80 years – 22.83%. The analysis of examinations showed major chronic illnesses as following: cataract (43.44%), glaucoma (28.61%), conjunctivitis (6.32%), AMD (5.89%) and eye injuries (2.35%). Eye injuries take fi fth position and are more frequent among men (81.63%). In most cases, it was related to mechanical and chemical injuries. Apart from the eyesight diseases, also refraction errors have been reported in the examined group. Hypermetropia accounted for 33.70%, astigmatism for 29.64% and myopia for 20.44%. Conclusions. Cataract, glaucoma, conjunctivitis and macular degeneration referring to age were the most frequent diseases occurring among examined group. Most often eye injuries relate to men